Intracorneal Hematoma Showing Clinical and Dermoscopic Features of Acral Lentiginous Melanoma. (8th May 2017) - Uslu, Ugur; Heppt, Franz; Erdmann, Michael
Abstract : Intra- and subcorneal hematoma, a skin alteration seen palmar and plantar after trauma or physical exercise, can be challenging to distinguish from in situ or invasive acral lentiginous melanoma. Thus, careful examination including dermoscopic and histologic assessment may be necessary to make the correct diagnosis. We here present a case of a 67-year-old healthy female patient who presented with a pigmented plantar skin alteration. Differential diagnoses included benign skin lesions, for example, hematoma or melanocytic nevus, and also acral lentiginous melanoma or melanoma in situ. Since clinical and dermoscopic examinations did not rule out a malignant skin lesion, surgical excision was performed and confirmed an intracorneal hematoma. In summary, without adequate physical trigger, it may be clinically and dermoscopically challenging to make the correct diagnosis in pigmented palmar and plantar skin alterations. Thus, biopsy or surgical excision of the skin alteration may be necessary to rule out melanoma.